Comfortable others: the process of identity niching among private employment agencies, employers and migrant domestic workers - Tame, Bianca (Department of Sociology, 2025)
This thesis explores the process of “identity niching” in the domestic work sector by focusing on the role of and demand for the services of private employment agencies (PEAs) that specialise in placements in Cape Town. The thesis focuses on how Zimbabwean migrant domestic workers' (MDWs) identity as “comfortable others”, which is associated with an ideal type of intimate work culture that employers and PEAs demand, is niched in recruitment and hiring practices. Using a qualitative research approach that included interviews with PEAs, MDWs and employers, and critical ethnography among MDWs, this thesis demonstrates how the demand for comfortable others is met through PEAs but also mobilized by MDWs to access “decent” work. The thesis draws on the cultural formations approach from the South and impression management theory to understand the relevance of intimacy and an intimate work culture in recruitment and hiring processes in post-apartheid South Africa. This thesis argues it is through the agency of employers and PEAs trying to find comfortable others and a seemingly compliant labour force that MDWs are “niched” in relation to South Africans. Further, it is through the agency of MDWs that ethno-cultural preferences associated with an intimate work culture are mobilized to gain employment. Yet how MDWs exercise their agency when mobilizing their intimate work culture, as a defensive combination and through their cultural formation, captures their journey through the underbelly of the domestic sector. Therefore, the findings show that the type of employments paths MDWs choose between, and their domestic work choices, illustrate simultaneous processes of accommodation and agency that are made explicit through the lens of an intimate work culture. It is the practical but publicly informed knowledge gathered through a series of relational but intentional interactions that influence the process of identity niching to meet the demand for comfortable others. However, when examining the different types of domestic work MDWs choose between – and also aspire to – employers that use PEAs appear to be comfortable others too, because they are likely to be labour compliant. Ultimately, the demand for comfortable others can be framed as a response to an “intimate workplace crisis” for PEAs (as employers too), and for employers and domestic workers. Further, the demand for comfortable others is context specific, arising from the particularities of a power-laden domestic employment relationship characterized by the tension between the public and private nature of the intimate workplace that domestic workers and employers iv experience. The analysis of the identity niching process reveals that the socio-legal context and experience of a “crisis of representation” and an “intimate workplace crisis” has given rise to the demand for PEAs in South Africa's post-apartheid domestic sector. The crisis of representation refers to employers' demand for support services in their mostly newfound role as labour compliant employers of domestic workers. For domestic workers, the crisis of representation is symbolic of the atomized nature of domestic work, the rise in underemployment and flexible work arrangements, and low trade union representation. This thesis contributes to making visible PEAs that specialize in placements, a notable departure from research that focuses on PEAs that offer housecleaning services. In addition, this thesis contributes to theorizing intimate work in the domestic sector and examining MDWs' cultural formations as a tool for mobilizing for decent work. The theoretical argument and the findings have potential for understanding the demand for different types and forms of intermediaries in the domestic sector in the context of fostering a culture of legal compliance that benefits domestic workers. The thesis concludes that intimacy is a distinct organizing principle of recruitment and hiring trends that informs the social construction of comfortable others among PEAs, MDWs and employers, and explains the fluid nature of hiring and recruitment patterns in the contemporary intimate workplace.